Influence of Minimally Invasive Resection Technique on Sphincter Preservation and Short-term Outcome in Low Rectal Cancer in the Netherlands. Issue 12 (December 2021) - Rutgers, Marieke L.; Detering, Robin; Roodbeen, Sapho X.; Crolla, Rogier M.; Dekker, Jan Willem T.; Tuynman, Jurriaan B.; Sietses, Colin; Bemelman, Willem A.; Tanis, Pieter J.; Hompes, Roel
Abstract : BACKGROUND: Transanal and robotic-assisted total mesorectal excision are techniques that can potentially overcome challenges encountered with a pure laparoscopic approach in patients with rectal cancer. OBJECTIVE: The aim of this study was to evaluate the proportion and predictive factors of restorative procedures and subsequent short-term outcomes of 3 minimally invasive techniques to treat low rectal cancer. DESIGN: This is a nationwide observational comparative registry study. SETTINGS: Patients with rectal cancer were selected from the mandatory Dutch ColoRectal Audit. PATIENTS: Patients with low rectal cancer (⩽5 cm) who underwent curative minimally invasive total mesorectal excision between 2015 and 2018 were included. MAIN OUTCOME MEASURES: The primary outcomes measured were the proportion of restorative procedure, positive circumferential resection margin, and postoperative complications. RESULTS: A total of 3466 patients were included for analysis, of which 33% underwent a restorative procedure. Resections were performed laparoscopically in 2845 patients, transanally in 448 patients, and were robot-assisted in 173 patients, with a proportion of restorative procedures of 28%, 66%, and 40%. The transanal approach was independently associated with a restorative procedure (OR, 4.11; 95% CI, 3.21–5.26; p < 0.001). Independent risk factors for a nonrestorative procedure, irrespective of the surgical technique, were age >75 years, ASA physical status ≥3, BMI >30, history of abdominal surgery, clinical T4-stage, mesorectal fascia ⩽1 mm, neoadjuvant therapy, and having a procedure in 2015 to 2016 versus 2017 to 2018. The circumferential resection margin involvement was similar for all 3 groups (5.4%, 5.1%, and 5.1%). Short-term postoperative complications were less favorable for the newer techniques than for the laparoscopic approach. LIMITATIONS: This study was limited because of the registry's variables and different group sizes. CONCLUSION: Patients with low rectal cancer in the Netherlands are more likely to receive a restorative procedure with a transanal approach, compared with a laparoscopic or robotic procedure. Short-term oncological outcomes are comparable between the 3 minimally invasive techniques. See Video Abstract at http://links.lww.com/DCR/B608 . INFLUENCIA DE LA TÉCNICA DE RESECCIÓN MINIMAMENTE INVASIVA CON PRESERVACIÓN DE ESFÍNTERES EN LA RESOLUCIÓN A CORTO PLAZO EN CANCER DE TERCIO INFERIOR DE RECTO EN LOS PAÍSES BAJOS: ANTECEDENTES: La excisión mesorrectal transanal y asistida por robot son técnicas que potencialmente pueden superar algunos obstáculos que podemos encontrar en un abordaje exclusivamente laparoscópico en pacientes con cáncer de recto. OBJECTIVOS: El objetivo de este estudio es evaluar la proporción y los factores de predicción positivos de los procedimientos restauradores y los resultados subsecuentes a corto plazo de tres técnicas mínimamente invasivas para tratar el cáncer de tercio inferior de recto. DISEÑO: Es un estudio comparativo observacional del registro nacional. ESCENARIO: Pacientes con cáncer de recto seleccionados del Registro Oficial de la Auditoría Holandesa Colo-rectal. PACIENTGES: Pacientes con cáncer de tercio inferior de recto (⩽5 centimetros) sometidos a excision mesorrectal total mínimamente invasiva curativa. PRINCIPALES PARAMETROS DE EFECTIVIDAD: Proporción de procedimientos restauradores, margen de resección circunferencial positivo y complicaciones postoperatorias. RESULTADOS: Se incluyeron un total de 3, 466 pacientes para análisis, de los cuales 33% fueron sometidos a procedimiento restaurador. Las resecciones fueron laparoscópica en 2, 845 pacientes, transanal en 448 y asistidas por robot en 173, con una proporción de procedimientos restauradores en 28%, 66% y 40% respectivamente. El abordaje transanal se correlacionó en forma independiente con el procedimiento restaurador (OR 4.11; 95% CI 4.11; 95% CI 3.21-5.26; p <0.001). Los factores de riesgo independientes para un procedimiento no restaurador, sin tomar en cuenta la técnica quirúrgica fueron: edad >75, American Society of Anesthesiologist ≥3, índice de masa corporal >30, antecedente de cirugía abdominal, Estadio clínico T4, fascia mesorrectal ⩽1 millimetro, terapia neoadyuvante y haber sido sometido al procedimiento en 2015-2016 y no en 2017-2018. El margen circunferencial de resección involucrado fue similar para los tres grupos (5.4%, 5.1% y 5.1%). Las complicaciones postquirúrgicas a corto plazo fueron menos favorables para las técnicas nuevas comparadas con el abordaje laparoscópico. LIMTANTES: El estudio tiene la limitación de las variables dependientes del registro y la diferencia entre el número de pacientes en cada grupo. CONCLUSION: Los pacientes con cáncer de tercio inferior de recto en Holanda se tratan con mayor frecuencia mediante un procedimiento restaurador transanal en comparación con los abordajes laparoscópico o robótico. Los resultados favorables desde el punto de vista oncológico a corto plazo son comparables entre las tres técnicas de invasión mínima. Consulte Video Resumen http://links.lww.com/DCR/B608 .